2019
DOI: 10.22159/ijap.2019.v11s1.18204
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Zoledronate Gel Emulsion in Virgin Coconut Oil

Abstract: Objective: This study aimed to analyze the physical stability and drug content of zoledronate (ZOL) gel emulsion in virgin coconut oil (VCO) as a newpharmaceutical product at 25°C as room temperature and 40°C as an accelerated temperature for a stability physics test.Methods: The ZOL gel emulsion comprises the following ingredients: 0.16% ZOL powder, 2% carboxymethyl cellulose, 5% VCO, 0.44% sodiumbenzoate, and 0.009% antioxidant butylated hydroxytoluene, and distilled water. Samples of this gel emulsion were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…One of the topical preparations with a local effect is emulgel. 16 The bisphosphonate risedronate in this study was modified as an emulgel with VCO as the oil phase in its preparation. The results revealed that the effectiveness was not much different from previous studies, namely a decrease in the distance of the relapse movement.…”
Section: Discussionmentioning
confidence: 99%
“…One of the topical preparations with a local effect is emulgel. 16 The bisphosphonate risedronate in this study was modified as an emulgel with VCO as the oil phase in its preparation. The results revealed that the effectiveness was not much different from previous studies, namely a decrease in the distance of the relapse movement.…”
Section: Discussionmentioning
confidence: 99%
“…Modern researchers involved in topical semi-solid dosage forms quality assessment use a limited set of techniques to test the spreadability (various modifications of the parallel-plate method or the "slip and drag" method are most often used) [5][6][7][8][9][10][11][12][13][14][15]. In each same study, the conditions of the experiment are often subjected to significant or minor changes (parameters such as the exposure time of the load, the mass of the load, the mass of the dosage form, and the size of the glass plates).…”
Section: Discussionmentioning
confidence: 99%
“…A weight (50-500 g) of 125 g is placed on top for 1 minute. Then the diameter of the sample between the plates is measured [7][8][9][10][11].…”
Section: Parallel-plate Methodsmentioning
confidence: 99%
“…Deployment ability was measured by the slope of the distribution equation of the diameter of the dispersion versus weight load. [ 3 5 ]…”
Section: Methodsmentioning
confidence: 99%